2020
DOI: 10.1155/2020/4784191
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Saving Virtual Machine Placement Method for User Experience in Cloud Environment

Abstract: Green computing focuses on the energy consumption to minimize costs and adverse environmental impacts in data centers. Improving the utilization of host computers is one of the main green cloud computing strategies to reduce energy consumption, but the high utilization of the host CPU can affect user experience, reduce the quality of service, and even lead to service-level agreement (SLA) violations. In addition, the ant colony algorithm performs well in finding suitable computing resources in unknown networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…To minimise energy consumption and fulfil uers' experience, an enhanced ant colony algorithm is used to propose an energy-saving VMP approach which attains a balance between user experience and energy consumption in data centres [9]. The original ant colony algorithm's pheromone and heuristic parameters were modified, ensuring that the improved algorithm may transition from a local to a globally optimal solution, avoiding the algorithm's early maturity.…”
Section: Nature/bio Inspired Methodsmentioning
confidence: 99%
“…To minimise energy consumption and fulfil uers' experience, an enhanced ant colony algorithm is used to propose an energy-saving VMP approach which attains a balance between user experience and energy consumption in data centres [9]. The original ant colony algorithm's pheromone and heuristic parameters were modified, ensuring that the improved algorithm may transition from a local to a globally optimal solution, avoiding the algorithm's early maturity.…”
Section: Nature/bio Inspired Methodsmentioning
confidence: 99%
“…They used mathematical modeling to place virtual machine cloud. Work described in [18] minimizes the network traffic for placing the virtual machines and compared their model with VMP algorithm, it is observed that their model reduced power energy consumption by 3.5%.…”
Section: International Journal On Recent and Innovation Trends In Com...mentioning
confidence: 99%
“…Cloud computing provides a compelling model for changing the work environment of IT companies, so cloud computing trends are on the rise. Among the various services in the cloud environment, IaaS includes Amazon, Google, and Microsoft, the leading commercial service providers that have developed a usage payment model based on this model to providers offer these services to users 1 . It takes a lot of PMs to meet the needs of cloud users and much energy to power and cool the various electronic modules within these systems 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The inactive servers go into the low-energy mode or are turned off to reduce the static energy consumption of servers, thus reducing the total energy consumption of the data center. However, before moving a VM, there are some important issues to consider: (1) the migration time of the virtual machine, that is, the trigger time; (2) the assortment of the VM to be migrated; and (3) which host should be selected to support the VM selected for relocation, that is, the host location.…”
mentioning
confidence: 99%